Humanización de la atención a la población en situación de desplazamiento. Programa de atención población desplazada. Atención psicosocial (2004)
ABSTRACT: The displacement, generated by effects of the violence and the armed conflict, besides to create alterations at economic, partner-political and material level, causes a fort psychological impact and of social organization who amerita a special attention. The psycho-social effects of the displacement are reflected particularly in three levels that is to say: the individual one, the relative and the communitarian one, presenting/displaying each one of them characteristic individuals.